Komunikasi Pembangunan Pemerintah Desa Aikmual Kecamatan Praya dalam Mengatasi Pengangguran Melalui Pelatihan Las - yulanda trisula yohanes; Lalu Wire Panggih (JCommsci - Journal Of Media and Communication Science, 2021)
The background of this research was Central Lombok experienced a decrease in unemployment, namely 2.44%. This reduction in the unemployment rate by the Village Government of Aikmual, Praya District can be overcome by welding training to village youth. It was made researcher known to find out the development communication carried out by the Aikmual Village Government in implementation of welding training. This is what makes researchers know to find out the development communication carried out by the Aikmual Village Government in implementing welding training. This type of research is qualitative with data collection techniques through interviews and documentation. The result of the research is that the implementation of development communication by the Aikmual Village Government applies four aspects, namely strength of the capacity of village youth, fairly and openly to the village youths to participate in activities, implementing controls empowerment through monitoring, and this activity is sustainable. The development, communication process in developing local communities involves aspects of the village government as a communicator or executor in program implementation, delivering development materials (training material), village youth as communicants, and the effects that village youths have after participating in treatment.